PERILAKU GEN Z PADA MASA PANDEMI COVID 19 - Ramayani Yusuf; Akmala Hadita (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2022)
Abstract— This study aims to determine the activity and behavior of gene Z during the covid 19 pandemic that has occurred since March 2020. The covid pandemic causes gene Z to be active at home with the enactment of government regulations to prevent the spread of Covid 19. This research is a qualitative research by taking 109 correspondences which are students at one of the universities in Bandung who are affected by the policy to study at home. The results of this study are useful for knowing the activities carried out by Gen Z in addition to distance learning activities. Gen Z does a lot of opening social media (IG, Tiktok, Reels, twitter) and exercising. The activity they want to do after this pandemic is over is gathering with friends. To reduce the risk of spreading covid 19, Gen Z should still pay attention to health protocols if you want to meet friends. Keywords: behavior, Gen Z, covid 19